PELAKSANAAN IBADAH HAJI ABAD KE 19 DAN DAMPAKNYA TERHADAP PERLAWANAN RAKYAT KEPADA KOLONIALISME BELANDA - Istikomah Istikomah (IAIN Syekh Nurjati Cirebon, 2017)
AbstractThe Hajj, in the 19th century, was a tool for transmitting religious culture and doctrine. The challenge that faced by prospective pilgrims is derived from the Dutch government as a pilgrims manager or administrator. Rules which applied before the departure until their arrival from Mecca (Holy Land) greatly complicate the congregation. The rise of social status after the pilgrimage had its own influence on society, the hajj had significant meaning and influence in the 19th century. It was able to mobilize the social and cultural forces against the Dutch. Therefore, the Dutch Indies government enacted a special policy related to pilgrimage whose purpose is to minimize the number of pilgrims from Indonesia. But in the end, the hajj policy doesn’t give a significant impact to the pilgrims. Therefore, still appears the resistance of Muslims led by Islamic leaders who has appellation “hajj”.Keywords: hajj, colonialism, resistance